Pengaruh Puasa Ramadhan Terhadap Tekanan Darah Dan Profil Lipid Pada Pasien Hipertensi Studi Kasus : Denpasar Selatan - I Wayan Happy Candra Dinata; Dhiancinantyan Windydaca Brata Putri; Gusti Ngurah Agung Windra Wartana Putra; I Gusti Ngurah Mayun (Indonesian Journal of Pharmaceutical Education, 2023)
Hypertension is the most common cardiovascular disease in society. Management of hypertension can be pharmacological and non-pharmacological. One of the nonpharmacological therapies for hypertension is fasting therapy. Ramadan fasting is fasting that is obligatory for Muslims and has been set in the month of Ramadan for one month (29 or 30 days). Fasting changes a person's eating and drinking patterns which affect the body's metabolism which results in increased production of angiotensinogen which impacts blood pressure and increases in High-density Lipoprotein cholesterol. The purpose of this study was to determine the effect of Ramadan fasting on blood pressure and lipid profiles in hypertensive patients. This study used a pre-experimental research design with the One Group Pretest-Posttest model. The sampling method used non-probability sampling with purposive sampling technique. Measurements were taken before the fasting month of Ramadan and one month of fasting. Data analysis using the Wilcoxon test. The results of the study in the form of systolic and diastolic blood pressure before fasting with one month of Ramadan fasting, the mean ± SD respectively were 145 ± 17.45 p-value (0.001); 87.70 ± 9.82 p-value (0.001). For lipid profiles (cholesterol, triglycerides, HDL, LDL) before fasting with one month of Ramadan fasting, the mean ± SD respectively were 181.60 ± 26.63 p-value (0.001); 113.65 ± 43.91 p-value (0.001); 53 ± 7.71) p-value (0.001); 116.30 ± 18.38 p-value (0.001). This study concluded that there was a decrease in systolic and diastolic blood pressure, and an improvement in fasting lipid profile levels during Ramadan fasting in hypertensive patients.